Analisis Kebijakan Pendidikan Islam dalam Meningkatkan Kualitas Pendidikan di Indonesia - Suharta; Zonya Rubeka Bawengan; Ahmad Subagyo; Muhamrnad Sofian (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Islamic education holds a strategic role in shaping character and enhancing the quality of human resources in Indonesia. Amid the complexity of a multicultural society and the ever-changing global landscape, Islamic education is compelled to undergo substantive transformation. This study analyzes the direction and implementation of Islamic education policies and evaluates their contribution to improving educational quality. Using a qualitative approach and literature-based method, data were collected from policy documents, scholarly publications, and relevant previous research. The findings indicate that the government has enacted several strategic measures, including madrasah revitalization, integrative curriculum strengthening, teacher competency development, and accreditation-based management reform. However, policy implementation at the institutional level faces various obstacles, such as inadequate infrastructure, low digital literacy, and suboptimal human resource support. The study underscores the importance of contextual, adaptive, and participatory policy formulation. Furthermore, collaboration among government, communities, and educational institutions is vital for reinforcing the role of Islamic education as a foundation for national character building. A more systemic and responsive approach to local needs and global challenges is expected to enable Islamic education to make a tangible contribution to the sustainable enhancement of national educational quality.